PENGARUH MODEL CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Nadiya, Mita; Tri Suarno, Dendi (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study aims to determine the effect of the Creative Problem Solving (CPS) learning model on elementary students’ critical thinking skills. The research employed a quantitative method with a pre-experimental design using a One Group Pretest-Posttest Design. The sample consisted of 30 fourth-grade students selected through purposive sampling. The research instrument was an essay test based on Bloom’s taxonomy levels C4 (analyzing), C5 (evaluating), and C6 (creating). Data were analyzed using the Shapiro–Wilk normality test and the Paired Sample t-Test for hypothesis testing. The results showed that the average pretest score was 65.67 and increased to 84.88 in the posttest. The hypothesis test result indicated a significance value of 0.000 < 0.05, meaning that there is a significant effect of the Creative Problem Solving learning model on students’ critical thinking skills. The CPS model enhances student engagement through systematic problem-solving processes, encouraging students to think critically, analytically, and reflectively.